Medicinal Plant Diversity in the Market of Cibinong and Ciluar, Bogor - Siti Susiarti; Nissa Arifa; Elis Napisatunnaqiah (Journal of Tropical Ethnobiology, 2021)
The pattern for documenting plants in various regions is a form of understanding theimportance of plant resources in society. Plant resources are a natural asset that used asmedicine, for example for the communities around Cibinong Market and Ciluar Market,Bogor. The purpose of this study was documenting species of plants, parts used andprocessing methods for medicinal plants. The used method was data collection and directobservation at Cibinong Market and Ciluar Market. Interviews were conducted directly withtraders of vegetables, spices and potpourri. The data from the observations showed 43 speciesof plants are used as medicine with an knowledge from generation to generation.